2022
DOI: 10.1111/joss.12787
|View full text |Cite
|
Sign up to set email alerts
|

Context‐sensitive thinking influences judgments of expected satiation from combinations of foods: The role of individual and cultural variations

Abstract: Prior research has suggested the influence of thinking styles in judgments of foods, with individual and cultural differences. Here, we tested whether context sensitivity may influence judgments of a food's basic characteristics (e.g., expected satiation) in the presence of other foods in the surrounding context. Given their greater sensitivity to contextual information, participants from Singapore (compared with the USA) perceived central/focal food items as more satiating when surrounded by other foods that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…In addition, Alnawas et al (2023) confirm that holistic (vs. analytical) thinking styles are more likely to weaken the negative impact of the severity of service failure on brand tolerance. Other studies have also confirmed the important role of different styles of thinking in consumer behavior decisions (Cheon et al, 2022;Monga & John, 2008). Based on the above literature, holistic (vs. analytical) people tend to consider more contextual factors related to the object and are more likely to evaluate the object in its broader context.…”
Section: Dose Et Al (2019)mentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, Alnawas et al (2023) confirm that holistic (vs. analytical) thinking styles are more likely to weaken the negative impact of the severity of service failure on brand tolerance. Other studies have also confirmed the important role of different styles of thinking in consumer behavior decisions (Cheon et al, 2022;Monga & John, 2008). Based on the above literature, holistic (vs. analytical) people tend to consider more contextual factors related to the object and are more likely to evaluate the object in its broader context.…”
Section: Dose Et Al (2019)mentioning
confidence: 76%
“…A review of the above literature shows that although many studies have explored how styles of thinking affect consumers' cognitive and decision‐making process (Cheon et al, 2022; Monga & John, 2008; Wang et al, 2023), however, few studies highlight the potential impact of styles of thinking on receivers' responses to the referrals. In this research, accordingly, we propose that holistic (vs. analytic) receivers are more likely to consider the contextual factors in RRPs (e.g., the presence of rewards and tie strength), which may result in different receiver responses to the referrals.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…For example, “Western” (analytic) individuals (e.g., Danes or U.S. Americans), compared to “Eastern” (holistic) individuals (e.g., Chinese people), focused more on the central aspect of the stimuli. Moreover, analytic and holistic cultures have been found to differ in perception of food-related stimuli ( Choi, 2016 ; Choi et al, 2020 ; Chrea et al, 2004 ; Togawa et al, 2019 ), scale usage ( Feng and O’Mahony, 2017 ; Yeh et al, 1998 ), variance consistency ( Beekman and Seo, 2023 ), and environmental effect ( Beekman and Seo, 2022 ; Cheon et al, 2022 ). These imply that the AH theory might offer insight into why consumer responses to identical test samples varied among groups of different cultures, especially “Western” versus “Eastern.”…”
Section: Introductionmentioning
confidence: 99%